Antimicrobial Resistance in Water in Latin America and the Caribbean: Available Research and Gaps - Moreno-Switt, Andrea I.; Rivera, Dacil; Caipo, Marisa L.; Nowell, David C.; Adell, Aiko D. (Frontiers in Veterinary Science, 2020)
Introduction: Antimicrobial resistance (AMR) is a public health concern that has gained increasing global awareness, and it is estimated that there will be 10 million deaths annually by 2050. The importance of the role of the environment in disseminating clinically relevant AMR is a concern. Although research on AMR in Latin America and the Caribbean (LAC) has been conducted, these data have not been analyzed together to better understand which areas in AMR have been more studied, and which require more attention. Objective: Determine the state of knowledge and identify the information gaps for AMR in water in LAC through an exploratory review that identifies the scientific articles that have addressed the topic. Method: The process of selecting scientific articles from databases consisted of the four phases of an exploratory review focusing on eight themes of interest. Results: The selection process identified 289 studies that were published between 1973 and October 2017, and these studies were included in the analysis. Most of the research was performed from 2008–2017. Brazil was the main contributor to the study of AMR in the region while no research was identified in AMR in water in eight of 18 of LAC countries. The most researched topics in water are phenotypic detection of AMR (theme VIII), detection of antimicrobial resistance genes (ARG) (theme V), and degradation of AMR (theme III). Limited research was identified on insects, agricultural products, aquatic organisms, livestock, and wastewater other than hospital wastewater. Research on emerging pests and diseases with a potential impact on the production of AMR (theme VII), impact of the use of antimicrobials on agricultural production (theme IV), and negative effects of AMR on wildlife (theme II) was scarce. Conclusions: We suggest to focus research efforts and resources to study themes VII, IV, II, I, and VI, for which there is little research in LAC, without hindering the valuable research conducted on themes VIII, V, and III. The AMR environmental situation is mainly driven by a few countries that are not representative of the LAC region, and therefore, research is needed in other LAC countries besides Brazil.